Implementation of Certainty Factor Method in Mental Health Diagnosis Expert System in Adolescents Aged 18 – 24 Years - Yenny Desnelita; Mario Cesar; Gustientiedina Gustientiedina; Alyauma Hajjah; Ramalia Noratama Putri (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
Mental health in adolescents aged 18-24 years is a real condition and a problem that has received less attention from parents or certain parties. Individual adolescents free from all forms of symptoms of mental disorders are one of the keys to maintaining a healthy body from mental health disorders . The group most vulnerable to mental health disorders is adolescents, where many adolescents do not receive the care they should from their parents. Expert systems can help solve problems in the field of mental health in adolescents aged 14-18 years as befits a psychiatrist by adopting expert knowledge into computers. This study aims to develop an expert system for diagnosing mental health disorders in adolescents aged 18-24 years using the Certainty Factor (CF) method by combining expert and user belief values in the diagnostic solutions provided later by the expert system. This study used five mental disorders in adolescents aged 18-24 years, namely depression, schizophrenia, bipolar, obsessive, anxiety disorders which were later given the weight of symptom beliefs and data on preventive solutions to the disease using the CF method . The results of the study are in the form of an expert system for diagnosing mental health in adolescents. using the CF method which displays the certainty value of expert knowledge diagnosis. Testing of the expert system application in this study uses the black-box method with valid test results used.